2017
DOI: 10.3389/fpsyg.2017.01191
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Cognitive Load in Embodied Learning Settings

Abstract: In recent years, research on embodied cognition has inspired a number of studies on multimedia learning and instructional psychology. However, in contrast to traditional research on education and multimedia learning, studies on embodied learning (i.e., focusing on bodily action and perception in the context of education) in some cases pose new problems for the measurement of cognitive load. This review provides an overview over recent studies on embodied learning in which cognitive load was measured using surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 80 publications
(123 reference statements)
3
53
0
1
Order By: Relevance
“…Generally speaking, the results support the claim that the language used in different surveys should match the learning task (as discussed by Skulmowski & Rey, 2017). In the context of activity‐based and interactive learning media, Skulmowski and Rey (2018) suggested a more task‐oriented approach based on Wilson and Golonka (2013) that recommends the use of task analyses.…”
Section: Implications Of the Measurement Of Extraneous Load In Interasupporting
confidence: 84%
See 4 more Smart Citations
“…Generally speaking, the results support the claim that the language used in different surveys should match the learning task (as discussed by Skulmowski & Rey, 2017). In the context of activity‐based and interactive learning media, Skulmowski and Rey (2018) suggested a more task‐oriented approach based on Wilson and Golonka (2013) that recommends the use of task analyses.…”
Section: Implications Of the Measurement Of Extraneous Load In Interasupporting
confidence: 84%
“…Skulmowski and Rey (2017) reviewed recent results concerning which methods of measuring cognitive load are the most appropriate for more complex learning environments centered around (bodily) activity and suggested that these types of environments require different types of cognitive load measurement techniques than other types of learning scenarios. Most importantly, Skulmowski and Rey (2017) distinguished (inter‐)active settings from more verbally‐oriented modes of instruction and hint at the possibility that cognitive load surveys featuring items targeted at the latter forms of instruction may not be appropriate for interactive learning. Based on Skulmowski and Rey (2017), we assume that the survey by Leppink et al (2013) may be more fitting for learning materials that primarily involve verbal contents.…”
Section: Conceptualizing and Measuring Extraneous Load In Interactivementioning
confidence: 99%
See 3 more Smart Citations